(untitled) (Biological Sciences - PJSIR, 2025)
The use of foliar applications to enhance crop growth and yield has become an important strategy in modern agriculture, particularly for fruit crops like muskmelon (Cucumis melo L.) known for its nutritional value and economic significance. This research focus on the growth, quality and yield of muskmelon was conducted at platoo Mardan, during 2018. The research was laid out in two factor Randomized complete block design (RCBD). Factor "A" consists of different zinc levels (0, 25, 50 and 75 ppm) while Factor "B" consist of different salicylic acid (SA) concentrations (0, 50, 100 and 150 ppm) which were applied as foliar application 40 days after sowing. The maximum fruit volume (12.40 cm3), rind thickness (0.28 mm) and total soluble solid (11.73 °Brix) were significantly affected by 75 ppm of zinc concentration. Whereas, the maximum number of branches (6.83), total yield/ha (12.61 tons) and fruit firmness (9.00 cm3) were recorded in plants treated with 50 ppm of zinc concentration. While salicylic acid the maximum yield/he (12.82 tons), fruit volume (13.18 cm3), rind thickness (0.28 mm), total soluble solid (10.62 °Brix) and fruit firmness (9.26 N) were recorded in plant treated with 150 ppm of salicylic acid. It can be concluded from the present results that the treatment of 75 ppm of zinc levels and 150 ppm of salicylic acid can improve the growth and production of muskmelon Cv. kandyalay under the agro. climatic condition of Mardan.